Pengaruh Locus of Control dan Need for Achievement Terhadap Niat Berwirausaha melalui Entrepreneurial Self Efficacy - Ananda, Lenny; Noviani, Leny (Jurnal Pendidikan Ekonomi (JUPE), 2024)
Psychological factors such as locus of control, need for achievement, and entrepreneurial self-efficacy are interesting to discuss in the context of fostering entrepreneurial intentions. This study aims to determine the impact of psychological factors, namely locus of control and need for achievement, on entrepreneurial intentions through entrepreneurial self-efficacy. The research method used is a quantitative survey with a sample consisting of 332 students. The sampling technique in this study employs proportionate random sampling, with data collected via questionnaires. Data analysis was conducted using descriptive statistics and hierarchical regression analysis. The results show that: 1) There is a positive and significant effect of locus of control on entrepreneurial self-efficacy; 2) There is a positive and significant effect of need for achievement on entrepreneurial self-efficacy; 3) There is a positive and significant effect of entrepreneurial self-efficacy on entrepreneurial intentions; 4) Entrepreneurial self-efficacy mediates the relationship between locus of control and need for achievement on entrepreneurial intentions. These findings highlight that increasing locus of control and need for achievement among students can enhance entrepreneurial self-efficacy, which in turn increases entrepreneurial intentions.